Competition and cooperation in expanding the demand base of natural gas for Russia and Qatar - Dang, Thi Quynh Trang (2014)
This study explores the hypothetical scenarios where Russia and Qatar diversify their supply into liquefied and pipeline natural gas respectively. A game theoretical approach is employed to study the strategic interactions among exporters and importers. The constructed models derive the equilibrium prices, quantities and profits.